2019
DOI: 10.1155/2019/5734018
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Series Analysis for Novel Spatiotemporal Pulse Waves: Normal, Taut, and Slippery Pulse Images

Abstract: In this article, a three-dimensional pulse image (3DPI) instead of a one-dimensional temporal pulse wave is studied to elucidate its spatiotemporal characteristics. To check the spatial and temporal properties of 3DPI, adopted is Fourier series, in which a ratio (r) is defined as one amplitude divided by the sum of the first three amplitudes of harmonics. A ratio sequence is constituted from 70 to 90 ratios in a heartbeat with 70–90 3DPIs by sampling. Twenty-four subjects (14 males and 10 females with age of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Twain). In addition, as described in Matos et al's review [8] and Peng et al's report [9], the HA of radial arterial waveforms could make a significant contribution to traditional Chinese medicine. Professors Tsai et al indicated that the harmonic characteristics of the radial artery in the wrist at different positions and different parameters were not identical, and recommended that any measurement location in future studies on the HA of pressure pulse diagnosis needs a more finely adjusted analysis [10].…”
Section: Introductionmentioning
confidence: 93%
“…Twain). In addition, as described in Matos et al's review [8] and Peng et al's report [9], the HA of radial arterial waveforms could make a significant contribution to traditional Chinese medicine. Professors Tsai et al indicated that the harmonic characteristics of the radial artery in the wrist at different positions and different parameters were not identical, and recommended that any measurement location in future studies on the HA of pressure pulse diagnosis needs a more finely adjusted analysis [10].…”
Section: Introductionmentioning
confidence: 93%
“…In recent years, some studies have shown that analysis of the three-dimensional radial pulse waves reflects the concept of multi-dimensional pulse condition in TCM [97][98][99]. In order to make the TCM more intuitive and convincing, Chen et al used the array sensor to measure the three-dimensional pulse wave, which is helpful for doctors to make more accurate diagnosis [98].…”
Section: Quantitative Analysis Of the Tcm Pulse Diagnosismentioning
confidence: 99%
“…In order to make the TCM more intuitive and convincing, Chen et al used the array sensor to measure the three-dimensional pulse wave, which is helpful for doctors to make more accurate diagnosis [98]. Peng et al used Fourier series to analyze three types of pulse images, which can quantize the pulse feeling in TCM [99].…”
Section: Quantitative Analysis Of the Tcm Pulse Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Second, two key point values of the pulse are detected and assigned to individualize the functions. In addition, three indices ω, rextra, and r4italicth based on hemodynamic knowledge 17,18 are proposed to verify the interpretability of the modeling characteristics.…”
Section: Introductionmentioning
confidence: 99%